Всюду разрешимые краевые задачи для неоднородного дифференциального уравнения второго порядка с переменными коэффициентами. (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2019)
In this paper discussed correct boundary value problems for 2-order in nonhomogeneous differential equation with variable coefficients in a finite interval. Then consider the case of a punctured a finite interval. Formulas are given data resolvent boundary value problems